VALIDATION OF HEAT TRANSFER SIMULATION MODELS FOR INJECTION MOULDING OF ABS IN ALUMIDE® TOOLING - MOSIMANYANE, KGOMOTSO DAVID (Bloemfontein: Central University of Technology, Free State, 2016)
In this research, a nylon/aluminium composite (Alumide®) material was investigated for its suitability to produce moulds for injection moulding through an additive manufacturing process. Literature shows that Alumide® has a low melting point, even lower than most polymer materials used in injection moulding. It also has a low thermal conductivity of 0.8 W/mK compared to 51.9 W/mK of steel, making it poor in heat transfer. In order for Alumide® to be used successfully for injection moulding tooling, effective cooling of the moulds need to be applied. This project aimed to validate Moldex3D and Sigmasoft injection moulding simulation software to predict the amount of heat that is transferred from the mould cavity to the mould thereby determining the effectiveness of a given water conformal cooling layout. Two case studies were conducted where Alumide® was used as a tooling material for injection moulding of Acrylonitrile Butadiene Styrene (ABS). The case studies addressed the cooling channel design, moulding parameters and mould temperature for Alumide®. Simulations were conducted using the mentioned software packages in order to design and analyse cooling for Alumide® moulds. Simulation mould temperature results were compared with the actual field test results in order to validate the simulation packages used. Recommendations were made in terms of cooling channel design for Alumide® moulds in order to prevent defects that appear on the inserts along the cooling channels.
Published Thesis